2015
DOI: 10.3923/ijds.2015.95.106
|View full text |Cite
|
Sign up to set email alerts
|

PA-PG-PL System in Dairy Animals and its Significance: A Review

Abstract: Animal husbandry plays an important role in strengthening the rural economy. Heat is a major constraint on animal productivity in the tropical belt and arid areas. Heat stress in dairy cows as all temperature-related forces encourage changes or adjustments which may occur from the cellular to the total animal level to help the cows stay away from physiological disorders and then to better adapt to an adverse thermal environment. Milk production is impaired as a result of the drastic changes in biological funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 49 publications
(58 reference statements)
0
1
0
Order By: Relevance
“…the higher level of plasminogen in the treatment group during the hh season indicated lower conversion of inactive plasminogen compound to active plasmin enzymes. It is well-documented that plasminogen conversion to plasmin is related to stressful conditions in lactating animals, which ultimately helps to reduce the lactation energy burden by reducing milk yield (haQUe et al, 2015). hence it may be concluded that the cooling system in the summer was effective in minimizing environmental stress in the buffaloes.…”
Section: Resultsmentioning
confidence: 99%
“…the higher level of plasminogen in the treatment group during the hh season indicated lower conversion of inactive plasminogen compound to active plasmin enzymes. It is well-documented that plasminogen conversion to plasmin is related to stressful conditions in lactating animals, which ultimately helps to reduce the lactation energy burden by reducing milk yield (haQUe et al, 2015). hence it may be concluded that the cooling system in the summer was effective in minimizing environmental stress in the buffaloes.…”
Section: Resultsmentioning
confidence: 99%